Corporate foundations in the mining industry: institutional challenges to private sector involvement in development - McElroy, C (2012)
This thesis investigates the rise and performance of corporate foundations in the mining industry. Corporate foundations work to distribute the benefits of mining activities in developing countries. They are a hybrid organizational form that is connected to the funding and founding corporation, and yet to different degrees they independently govern their resources and activities. In addressing the problem of uneven benefit distribution, they are related to a growing interest in improved corporate social responsibility. This thesis examines corporate foundations’ forms and functions from an economic geography perspective that situates their rise and performance within the diversity and heterogeneity of economic activities that formulate the current context of the political economy of the mining industry. Through an overarching framework of organization and institutional theory the thesis investigates if: 1) corporate foundations in the mining industry are fit for purpose; 2) how the form of corporate foundations influences function, and vice-versa; and 3) how are these foundations shaped by, and in turn shaping, their (corporate/local/regional/national economic/regulatory/political/social) environments? It finds that corporate foundations in the mining industry currently lack a larger strategy to articulate the goal of their long-term performance. This is based on the findings of the empirical chapters that: 1) the organizational legitimacy of corporate foundations is particularly related to their form; 2) that problems of local failure to distribute benefit are an underdeveloped aspect of the resource curse, and requires close coordination with the technical changes of the mining industry and their effects on the regional population to manage; 3) that corporate foundations represent the path dependency of the mining industry, but when operated with a specific strategy for change are able to affect evolutionary institutional change in corporations; and 4) that the hybrid form of corporate foundations is best suited to build capacity and foster partnerships that facilitate processes of regional economic development through improved economic linkages with the mining industry. From these findings, the conclusion proposes that corporate foundations should adopt a strategy to serve as a mediator between mining corporations and the region to build institutional capacities and partnerships to facilitate the distribution of benefits from mining.